-3=n/4-6

Simple and best practice solution for -3=n/4-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=n/4-6 equation:



-3=n/4-6
We move all terms to the left:
-3-(n/4-6)=0
We get rid of parentheses
-n/4+6-3=0
We multiply all the terms by the denominator
-n+6*4-3*4=0
We add all the numbers together, and all the variables
-1n+12=0
We move all terms containing n to the left, all other terms to the right
-n=-12
n=-12/-1
n=+12

See similar equations:

| 7/8-3/4=k | | r/2+5=-5 | | r/2+5=5 | | 4=b/4+2 | | 3*1/4=k | | b/3-6=-1 | | -0.3y=2.1 | | m/5+7=9 | | 52,800+43,757+121,113+57,532+44,471+h=354,386 | | -0.5-0.3y=2.1 | | 4(2y+3)=84 | | 78-v=292 | | 5+4y=54-3y | | -8y−3.74=-8.3y−6.26 | | -10-3x=35 | | 4y-6=2y+30 | | -86=-6-4x | | 9-(2z-3)=5-3z | | 0.5-0.3y=2.1 | | 38-10x=10-4x | | 10=n/18=9 | | 94=-2y-6+12y | | 17k+3-8=18k+14 | | 22=1-7x | | 3y+5+4y=40 | | -5=-4+m/16 | | 95=5+3y | | -9(x+6)+4(1-5x)=-30(x+1)-5 | | -6=x/2-3 | | 5x+2.6=9.6 | | (x+2)^2-x^2=20 | | 2y-10=56 |

Equations solver categories